Blockchain-enabled Carbon Dioxide Removal: A Decentralized Framework for Transparent and Scalable Climate Mitigation - CHEN, Zihan; LI, Jia (European Journal of Sustainable Development, 2025)
Carbon Dioxide Removal (CDR) technologies are pivotal for achieving global climate targets, yet their scalability and operational efficiency remain constrained by fragmented data management, energy-intensive processes, and insufficient transparency in carbon accounting. This study explores the integration of consortium blockchain technology into CDR systems to tackle the barriers, emphasizing its potential to enhance environmental sustainability. A hybrid blockchain framework is proposed, combining decentralized governance with IoT-enabled monitoring to improve data integrity, automate carbon footprint verification, and optimize energy consumption across CDR operations. Key innovations include a dynamic consensus mechanism for real-time stakeholder collaboration and cryptographic protocols for secure, auditable record-keeping. Initial simulations demonstrate a 22-30% reduction in administrative overheads and a 15% improvement in data accuracy compared to conventional systems, highlighting the model’s capacity to strengthen accountability in emissions reporting. By enabling interoperable, tamper-proof data sharing, the system fosters trust among policymakers, investors, and technology providers—critical for accelerating NET deployment under the Paris Agreement. This work advances the discourse on digital solutions for climate action, offering a scalable architecture to align CDR implementation with sustainable development goals. Further validation through industrial pilots will refine its economic and technical feasibility. Keywords: Carbon Dioxide Removal, Blockchain, , SustaCarbon Emissions Reductioninability, Consensus Mechanism